2011
DOI: 10.1002/adsc.201100187
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid‐Catalyzed Dihydroxylation of Olefins in Aqueous Medium

Abstract: Abstract:The trans-dihydroxylation of olefins occurs efficiently by aqueous hydrogen peroxide catalyzed by p-toluenesulfonic acid at 50 8C, allowing the catalyst reuse and an outstanding substrate functional group tolerance such as tert-butoxycarbonylamino (BocNH), benzyloxycarbonylamino (CbzNH), benzyloxy (OBn), tosyloxy (OTs), hindered ketal, (2-trimethylsilyl)ethoxymethoxy (OSEM), benzylamino (NBz), benzyloxy (OBz) and free amino acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…[20][21][22] The H 2 O 2 assisted cyclohexene oxidation to 1,2-diol in a catalytic route has been also reported over a set of homogeneous and heterogeneous catalysts. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] For example, Usui et al 26 reported a maximum diol yield of 98% in a solvent-and metal-free cyclohexene oxidation using H 2 O 2 , catalyzed by immobilized sulfonic acids. In another work, Rosatella et al 27 reported the application of Brønsted acids in the catalytic conversion of cyclohexene to diol.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] The H 2 O 2 assisted cyclohexene oxidation to 1,2-diol in a catalytic route has been also reported over a set of homogeneous and heterogeneous catalysts. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] For example, Usui et al 26 reported a maximum diol yield of 98% in a solvent-and metal-free cyclohexene oxidation using H 2 O 2 , catalyzed by immobilized sulfonic acids. In another work, Rosatella et al 27 reported the application of Brønsted acids in the catalytic conversion of cyclohexene to diol.…”
Section: Introductionmentioning
confidence: 99%
“…When we tested substrate 10 a , which has a labile aldehyde group, we were pleased to find that target molecule substrate 11 a was also cleaved smoothly under green light irradiation to give desired ( S )‐1‐phenylethanol 11 b with only slightly diminished ee (entry 10). We found that alkenes fell outside the substrate scope of the protocol, owing to the known acid‐catalyzed dihydroxylation of the double bond 22. However, the terminal alkyne of substrate 12 a was compatible with the protocol, and corresponding alcohol 12 b was obtained in moderate yield (entry 11).…”
Section: Methodsmentioning
confidence: 99%
“…The cascade epoxidation of olefin 1 with peracetic acid and an intramolecular epoxide opening reaction provided γ -butyrolactone 2 . TfOH was proposed as a catalyst in both the ring-opening reaction via epoxide activation and acetylation of the subsequent hydroxyl group of γ -butyrolactone [ 74 ]. This method was applied to intramolecular lactonization as well as the intermolecular diacetylation of olefins.…”
Section: Synthesis Of γ -Butyrolactonesmentioning
confidence: 99%